Reducing lower extremity amputations due to diabetes: The application of diabetic-foot protocol in Chiang Mai University Hospital - Rerkasem K. (2014)
The aim of this study was to determine whether intensive treatment and education strategies for diabetic patients with ulcers help in preventing leg amputation. From August 2005 to March 2007, a diabetic-foot protocol using a multidisciplinary approach was applied at our hospital. All the subjects were educated regarding diabetic-foot disease and its complications and prevention. This report compares the amputation rate in patients receiving the protocol care from August 2005 to March 2007 with those who had standard care from August 2003 to July 2005. Seventy-three and 110 diabetic-foot ulcer patients received protocol and standard foot care, respectively. The incidence of major amputations in the protocol and standard care groups was 4.1% and 13.6%, respectively (P =.03). Our protocol was associated with improved diabetic-foot care outcomes. It can be used by any hospital to improve outcomes for patients with diabetes. © 2008 Sage Publications.